PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, KEPUASAN KERJA DAN KOMPETENSI TERHADAP KOMITMEN ORGANISASI - Nurlaely Manurung; Asri Laksmi Riani (Universitas Muhammadiyah Surakarta, 2016)
The purpose of this study to determine and analyze the effect of work discipline, work motivation, job satisfaction, and work competence of the organization’s commitment to employees in RSO Prof. Dr. R Soeharso Surakarta. This research was explanatory research with survey research design. Data used primary data. The population of all employees who work in RSO Prof. Dr. R. Soeharso totaling 626 people, were taken a sample of 244 people with purposive sampling technique. The research instrument used a questionnaire with a scale linkert. The data analysis includes validation test, reliability and multiple regression analysis, t-test, F and R2. The results showed discipline work positive and significant effect on organizational commitment, motivation positive and significant effect on organizational commitment, job satisfaction positive and significant effect on organizational commitment, competence work positive and significant effect on organizational commitment, and the discipline of work, work motivation , job satisfaction and work competence significant effect together against the organization’s commitmentto employee hospital Orthopedics Prof. Dr. R. Soeharso Surakarta